The Role of Digital Microfinance in Enhancing Financial Inclusion and Poverty Alleviation - Choubey, Rajeev Ranjan; Sugandha, Sapna; Gupta, Shree Bala; Chaurasiya, Sneha (The Gaze: Journal of Tourism and Hospitality, 2024)
The integration of digital technologies into microfinance has the potential to enhance financial inclusion and alleviate poverty in developing countries significantly. This study explores the impact of digital microfinance services, such as mobile payment systems, digital wallets, and online platforms, on access to financial products for underserved populations and their role in economic development. By analyzing secondary data from academic literature, international reports, and case studies, the research identifies the benefits of digital microfinance, including reduced transaction costs, increased access to financial services, and improved economic opportunities for low-income households. However, the study also highlights significant challenges, such as technological barriers, regulatory hurdles, infrastructural limitations, and consumer awareness issues that hinder the widespread adoption and effective implementation of digital microfinance. The findings emphasize the need for strategic investments in digital infrastructure, enhanced digital literacy, and supportive regulatory frameworks to overcome these challenges. The research underscores the importance of digital microfinance in empowering individuals and communities to break the cycle of poverty and contribute to inclusive economic growth.